Mantenimiento y diagnóstico de fallas en vehículo eléctricos (2023)
This research addresses the problem of the lack of training and specialized services in fault identification and maintenance of electric vehicles in the country, contributing to sustainable electric mobility in the country. The Research and Development Group in Electromechanical Systems GridsE, through this work, seeks to strengthen electric mobility in the country through training in testing and maintenance of electric vehicles, as well as offering specialized services in repair and maintenance. A maintenance and fault diagnosis manual for electric scooters and motorcycles was developed, using basic test equipment such as multimeters and an Ebike Tester device, so that society in general can perform this maintenance and encourage the use of this type of vehicles.  The main conclusion of the work is the contribution in the training of specialized personnel for the maintenance of electric vehicles, to promote electric mobility in the country, being a significant contribution to society, as well as to encourage the creation of specialized workshops in electric vehicles, which the country requires. Finally, it is important to implement training programs and promote the creation of specialized workshops in electric mobility in order to contribute to electric mobility in Colombia.